Disaster Risk Finance Country Note : Uzbekistan - World Bank (World Bank, Washington, DC, 2020)
This disaster risk finance country note was prepared within the Uzbekistan strengthening disaster resilience technical assistance. It aims at: (a) raising awareness about fiscal impacts of disasters in Uzbekistan; (b) providing an overview of the way the Government of Uzbekistan (GoU) currently finances disaster losses; and (c) identifying potential measures to strengthen financial protection against disasters. The GoU has a number of regulations that govern post-disaster financing. They include provision that the first line of defense against natural disasters lies with the local level, while resources of a national reserve fund of the cabinet of ministers are drawn only when the local resources are exhausted. Therefore, the GoU can consider the following major steps to strengthen post-disaster financing in Uzbekistan: (a) improving collection of information related to disasters and accounting for fiscal risks; (b) developing a financial protection strategy against natural disasters; (c) improving disaster insurance; better understanding disaster insurance market in the country is an important first step; and (d) improving effectiveness and targeting of the resources available.